2006
DOI: 10.1007/s10551-006-9164-8
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Roles on U.S. Fortune 500 Boards: Director Expertise and Committee Memberships

Abstract: This study examines the presence and roles of female directors of U.S. Fortune 500 firms, focusing on committee assignments and director background. Prior work from almost two decades ago concludes that there is a systematic bias against females in assignment to top board committees. Examining a recent data set with a logistic regression model that controls for director and firm characteristics, director resource-dependence roles and interaction between director gender and director characteristics, we find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(160 citation statements)
references
References 43 publications
6
144
1
2
Order By: Relevance
“…Further, Mclntyre, Murphy and Mitchell (2007), and Taylor (1975) (2011) using a sample of 100 domestic companies by market capitalisation in Australia, Hong Kong, India, Malaysia, New Zealand and Singapore shows that more than 70% of the boards in these countries, except for Australia, have no female independent directors. Peterson and Philpot (2007) examine the role of female directors of the US Future 500 firms and show that female directors are less likely to sit on the executive committee, and are more likely to sit on the public affairs committee. However, there is no gender bias in director assignment to other board committees.…”
Section: Multiple Directorshipsmentioning
confidence: 99%
“…Further, Mclntyre, Murphy and Mitchell (2007), and Taylor (1975) (2011) using a sample of 100 domestic companies by market capitalisation in Australia, Hong Kong, India, Malaysia, New Zealand and Singapore shows that more than 70% of the boards in these countries, except for Australia, have no female independent directors. Peterson and Philpot (2007) examine the role of female directors of the US Future 500 firms and show that female directors are less likely to sit on the executive committee, and are more likely to sit on the public affairs committee. However, there is no gender bias in director assignment to other board committees.…”
Section: Multiple Directorshipsmentioning
confidence: 99%
“…Number of board committees is construed as an indicator of quality of board task performance and we measure it as a count of the number of board sub-committees (Peterson and Philpot, 2007). Delegating particular board functions into sub-committees enhances the quality with which boards can perform their roles (Ruigrok, Peck, Tacheva, Greve and Hu, 2006): for example, nominating directors and top managers (nomination committee), monitoring internal control and audit processes (audit committee), and providing properly incentivising, executive director pay packages (remuneration committee).…”
Section: Control Variablesmentioning
confidence: 99%
“…Three notable studies have helped our understanding of women's place on the board and its associated board committees. Kesner (1988) conducted the first study, and Bilimoria and Piderit (1994) and Peterson and Philpot (2007) conducted the second and the third where both studies revisited Kesner's original work. Kesner (1988) conducted an analysis of board committees' composition in terms of gender, tenure and occupational background.…”
Section: Empirical Research On Female Board Directorsmentioning
confidence: 99%
“…Conyon and Mallin (1997) in their review of female board participation of FTSE 350 companies found that of the eligible women on the board, 50 percent of them were involved in board committee work. Peterson and Philpot (2007) studied the firms on the Fortune 500 list from 2003. Using a sample of 487 firms, they found that women were represented on the board of 88 percent of the firms in the sample, and further that women were less likely to serve on the executive committee and more likely to be represented on the committees concerned with public affairs.…”
Section: Empirical Research On Female Board Directorsmentioning
confidence: 99%
See 1 more Smart Citation